2017
DOI: 10.20396/san.v24i1.8648035
|View full text |Cite
|
Sign up to set email alerts
|

Boas práticas em serviços de alimentação escolar

Abstract: Objetivou-se avaliar as boas práticas nos serviços de alimentação escolar da rede municipal de um município do Vale do Taquari, Rio Grande do Sul. Foram avaliadas 13 escolas de ensino fundamental por meio da Portaria nº 78/2009, a qual constitui um checklist composto por 153 critérios de avaliação distribuídos em 12 categorias. Os dados foram analisados no software SPSS Statistics da IBM®, versão 20.0, considerando o nível de significância de 5% (p<0,05). Foram observados maiores percentuais de conformidade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
2
0
4
Order By: Relevance
“…In block 3, the use of incomplete uniforms and adornments can be seen, diverging from the recommendations of the current legislation RDC 216/2004 ( 23 ) guides employers to provide enough uniforms for daily change ( 23 ). Another study ( 43 ) identified a different percentage of compliance, 71.78%, but the evaluated items were similar to our study. In our study, the item with the highest percentage of compliance was using caps, which kept the hair wholly protected.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In block 3, the use of incomplete uniforms and adornments can be seen, diverging from the recommendations of the current legislation RDC 216/2004 ( 23 ) guides employers to provide enough uniforms for daily change ( 23 ). Another study ( 43 ) identified a different percentage of compliance, 71.78%, but the evaluated items were similar to our study. In our study, the item with the highest percentage of compliance was using caps, which kept the hair wholly protected.…”
Section: Discussionsupporting
confidence: 83%
“…The authors reported that the SFS had good hygiene practices manual and SOP, but the documents were not available to the food handlers. Another study ( 43 ) identified 42.85% of SFS with good hygiene practices manual. Documents must be available for handlers to verify that activities are carried out with proper procedures.…”
Section: Discussionmentioning
confidence: 99%
“…São colocadas etiquetas com a identificação dos tipos de produtos, prevenindo a contaminação do ambiente por agente es químicos, favorecendo a eficiência dos procedimentos de limpeza. Nunes et al (2017) notaram que os serviços de alimentação demonstraram maior percentual de não conformidade devido à falta de telas de proteção nas portas e janelas, assim como, falta de controle para evitar o abrigo de pragas. Neste sentido, os serviços de alimentação necessitam de medidas preventivas por serem muito atrativos para a infestação de pragas e vetores.…”
Section: Resultsunclassified
“…A qualidade das instalações e edificações dos estabelecimentos de serviços de alimentação tem alta relação com a precaução de contaminações do alimento, sendo que as instalações devem ser estruturadas de forma a evitar cruzamentos entre áreas limpas e contaminadas e devem ser mantidas em condições adequadas de higiene (Nunes, Adami & Fassina, 2017). Ferreira et al (2011) consideraram que aqueles estabelecimentos que possuem estruturas planejadas e que mantem uma rotina de higienização, são capazes de garantir controle eficiente de pragas, protegendo assim os alimentos.…”
Section: Formas De Garantir a Segurança Dos Alimentos Nos Serviços Alimentíciosunclassified